Advertising on Social Media and Benefits to Brands - Ohajionu, Uchechi Cynthia; Mathews, Soney (2015)
Social media has expedited unparalleled growth in human interaction in modern times. This new media has caught the attention of organisations, communities and individuals through their ability to facilitate the collaboration of virtual communities and to provide a productive environment for mutual sharing and interaction. The adoption of social media for advertising by corporations worldwide is on the rise. Many corporations today have official Facebook pages, Twitter accounts as well as corporate blogs. All these are signs that social media has become a vital part of consumers‟ daily lives as well as the day-to-day operations of corporate organisations. The purpose of this conceptual paper is to examine the various tools that companies may use in their advertising aspect to increase their service and quality for their customers and increase profit. This study also seeks to provide insights on the social media use of Generation Y consumers in Malaysia.